Formulation, Characterization and Stability of Ibuprofen-Loaded Self-Nano Emulsifying Drug Delivery System (SNEDDS) - Yandi Syukri; Hannie Fitriani; Herianto Pandapotan; Bambang Hernawan Nugroho (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2019)
Ibuprofen is a poorly water-soluble drug with analgesic, antipyretic and anti-inflammatory effects. Self-Nano Emulsifying Drug Delivery System (SNEDDS) formulation is a solution to improve the solubility and bioavailability of ibuprofen. This research purposed to perform a formulation, characterization, and stability studies of ibuprofen-loaded Self-Nano Emulsifying Drug Delivery System (SNEDDS). Screening of ibuprofen SNEDDS was prepared by ternary diagrams for the chosen co-surfactants, surfactants, and oil. The following was characterizations of droplet size, zeta potential, and clarity. The solubility test for the determination of co-surfactant, surfactant, and oil obtained Propylene glycol monocaprylate (Capryol-90), Polysorbate 20 (Tween 20) and PEG 400. The screening of SNEDDS showed nine formulas (compositions) in the range concentration of Propylene glycol monocaprylate (1-3 mL), Polysorbate 20 (4-8 mL), and PEG 400 (1-3 mL). The composition of Propylene glycol monocaprylate (1-2 mL), Polysorbate 20 (5-8 mL) and PEG 400 (1-3 mL) passed the thermodynamic stability test. The test of robustness to dilution and stability study indicated that the formula with Propylene glycol monocaprylate, Polysorbate 20 and PEG 400 with the ratio of 1: 8: 1 and 1: 7: 2 was more stable. In conclusion, the stable ibuprofen SNEDDS could be prepared with Propylene glycol monocaprylate, Polysorbate 20, and PEG 400.